2014
DOI: 10.3171/2014.3.spine121018
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the L-4 vertebral body after use of a stand-alone interbody fusion device in degenerative spondylolisthesis for anterior L3–4 fixation

Abstract: Many studies attest to the excellent results achieved using anterior lumbar interbody fusion (ALIF) for degenerative spondylolisthesis. The purpose of this report is to document a rare instance of L-4 vertebral body fracture following use of a stand-alone interbody fusion device for L3–4 ALIF. The patient, a 55-year-old man, had suffered intractable pain of the back, right buttock, and left leg for several weeks. Initial radiographs showed Grade I degenerative spondylolisthesis, with instability in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(40 reference statements)
2
6
0
Order By: Relevance
“…Zeng et al [7] reported a rate of cage subsidence with standalone OLIF of 36.3%, higher than in the combined OLIF group (29.9%). Good clinical results of the OLIF without additional posterior pedicle screw fixation have been reported, but an indication was the absence of endplate damage [8][9][10][11]. Although the sample size was small in the present study, our results are supported by Zeng et al [7] and the main reason for cage subsidence is probably endplate damage during surgery.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Zeng et al [7] reported a rate of cage subsidence with standalone OLIF of 36.3%, higher than in the combined OLIF group (29.9%). Good clinical results of the OLIF without additional posterior pedicle screw fixation have been reported, but an indication was the absence of endplate damage [8][9][10][11]. Although the sample size was small in the present study, our results are supported by Zeng et al [7] and the main reason for cage subsidence is probably endplate damage during surgery.…”
Section: Discussionsupporting
confidence: 70%
“…It remains controversial as whether internal fixation is required for OLIF [7]. The standalone OLIF approach is associated with small trauma and short operation time and hospital stay [8][9][10][11]. Zeng et al [7] suggested that the rate of complications was lower with the use of combined screw fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OLIF has relatively broad indications, its procedure relays on small incision, it brings low risk of post-treatment trauma or bleeding and offers good stability and quick recovery. The stand-alone approach has shown the ability to reduce trauma, to greatly reduce the operation time, and to further promote the clinical application of OLIF [6][7][8][9] . Anatomy and clinical research indicates that the oblique lateral interbody fusion does not damage sacrospinalis and does not affect the endorhachis and the nerve root compared with traditional posterior lateral interbody fusion (PLIF, TLIF) [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of vertebral body fractures related to stand-alone cages with integrated screws. [19][20][21][22] In these cases, the exact mechanism for the failures was not discerned but most were operated on for spondylolisthesis and another had bilateral spondylolysis not appreciated prior to surgery. One should carefully assess the grade of spondylolisthesis, segmental instability, and the angulation of the disc space to be treated when deciding to perform stand-alone ALIF vs ALIF with posterior fixation.…”
Section: Discussionmentioning
confidence: 99%